In the problem below, which line contains an error? Circle your answer Line 1: − 5(x − 3) − 2x = 46 − 4(x + 1) Line 2: − 5x + 15 − 2x = 46 − 4x − 4 Line 3: − 3x + 15 = − 4x + 42 Line 4: x + 15 = 42 Line 5: x = 27 In which line you chose why is it wrong?

Respuesta :

Answer:

Line 3 is incorrect

Step-by-step explanation:

Required

Which line is wrong and why

Line 1: [tex]-5(x - 3) - 2x = 46 - 4(x + 1)[/tex]

Open brackets

Line 2: [tex]-5x + 15 - 2x = 46 - 4x - 4[/tex]

Collect like terms

[tex]- 2x-5x + 15 = - 4x - 4+46[/tex]

Simplify:

Line 3: [tex]-7x + 15 = - 4x +42[/tex]

According to the question, the line 3 is:

Line 3: − 3x + 15 = − 4x + 42

This is incorrect because -5x - 2x = -7x; and not -5x - 2x = 3x as seen in the question